2022
DOI: 10.1111/nuf.12715
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies at the frontline of care: Comparisons between Covid‐19 and non‐Covid‐19 units' nurses and the role of moderator variables

Abstract: Introduction Relatively few studies focused on the coping strategies adopted by the healthcare workers during the second phase of the pandemic. The present study compared the coping strategies between Italian nurses working in Covid‐19 and in other units and it explored whether socio‐demographic and work‐related variables moderate the relation between the type of unit and coping strategies. Methods A web‐based questionnaire that included sociodemographic and work‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
(203 reference statements)
2
4
0
Order By: Relevance
“…A combination of increased emotional exhaustion, perceived stress, anxiety, chronic fatigue, and reduced personal achievement and inter-shift recovery suggest higher level of occupational stress and burnout among nurses working in COVID units than nurses in non-COVID units. This is in line with prior work which demonstrated that the uncertain treatment outcomes of COVID patients and the fear of getting infected induce stress and burnout among nurses working with COVID patients [19].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A combination of increased emotional exhaustion, perceived stress, anxiety, chronic fatigue, and reduced personal achievement and inter-shift recovery suggest higher level of occupational stress and burnout among nurses working in COVID units than nurses in non-COVID units. This is in line with prior work which demonstrated that the uncertain treatment outcomes of COVID patients and the fear of getting infected induce stress and burnout among nurses working with COVID patients [19].…”
Section: Discussionsupporting
confidence: 91%
“…For example, Yoon et al [16] documented the increased stress among healthcare providers due to the 'spillover' or the indirect effects of COVID-19 on the vulnerable non-COVID patients resulting in treatment disparities towards chronically ill and mental health patients. Furthermore, studies have supported that nurses who cared for non-COVID patients experienced higher levels of anxiety, PTSD symptoms, neuroticism and poor coping strategies compared to the COVID unit nurses [17][18][19]. Similarly, Doo et al [20] found that the nurses in COVID units working with COVID-suspected patients suffered significantly higher anxiety, depression, and low resilience than nurses working with COVID-positive and non-COVID patients due to the increased uncertainty of infection risk and insufficiently protective equipment and environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Romero-García et al (2022) found that avoidance-oriented coping styles, such as self-distraction, substance use, and self-blame, predicted anxiety and depression, but the choice of coping style has been associated with demographic characteristics. Some studies examining the coping styles of healthcare workers during the COVID-19 pandemic have found that the choice of an avoidance-oriented coping style is associated with age, education, marital status, and years of service as a nurse ( Kowalczuk et al, 2022 , Righi et al, 2022 ). In other words, coping style might mediate the effect of demographic characteristics on anxiety and depression.…”
Section: Dear Editormentioning
confidence: 99%